ANALYSIS OF MEASURE-MEASURES AND ACHIEVED RESULTS TO IMPLEMENT MECHANISMS OF INITIATIVE BUDGETING (Marketing Journal, 2025)
This article presents legal and analytical information on the work carried out within the framework of the «Initiative Budget» process conducted this year through the «Open Budget» information portal organized by the Ministry of Finance of the Republic of Uzbekistan, proposals submitted by citizens, voting processes and cases of financing proposals recognized as winners, as well as on the work done within the framework of the «Open Budget» project.
Keywords: initiative budget; Open budget; Citizensʼ budget; information portal; state budget; Citizensʼ opinion